2019
DOI: 10.21203/rs.2.15707/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sarcopenia and intramuscular fat deposition are associated with poor survival in Indonesian patients with hepatocellular carcinoma: a retrospective study

Abstract: Background: A large-scale Japanese study showed that low skeletal muscle index (SMI) and intramuscular fat (IMF) deposition are associated with hepatocellular carcinoma (HCC) survival. Here, we evaluated the effects of SMI and IMF on the survival of Indonesian HCC patients, whose characteristics differ from those of Japanese patients. Methods: SMI and mean muscle attenuation (MA) were evaluated using computed tomography images of the third lumbar vertebra (L3) in a prospective cohort of 100 Indonesian HCC pati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 30 publications
0
16
0
1
Order By: Relevance
“…to stratify patients into those with low and high SMD. In the remaining 17 studies assessing SMD, threshold values used ranged from ≤22.0 HU 23 to ≤44.4 HU 24–26 in male patients and ≤23.5 23 to ≤39.3 24 in female patients. Similar to their analysis of SMI, Aleixo et al reported the proportion of patients with low SMD across multiple thresholds 23 .…”
Section: Resultsmentioning
confidence: 99%
“…to stratify patients into those with low and high SMD. In the remaining 17 studies assessing SMD, threshold values used ranged from ≤22.0 HU 23 to ≤44.4 HU 24–26 in male patients and ≤23.5 23 to ≤39.3 24 in female patients. Similar to their analysis of SMI, Aleixo et al reported the proportion of patients with low SMD across multiple thresholds 23 .…”
Section: Resultsmentioning
confidence: 99%
“…The reason(s) for this discrepancy remain(s) unclear but sarcopenia could be a possible explanation. Sarcopenia is a prognostic factor for Asian patients with HCC [297,[299][300][301][302][303][304][305], while physical activity is reported to be associated with better survival in patients with HCC [306]. Thus, an important aspect of management is by considering body composition that includes body fat and skeletal muscle mass, when treating patients with HCC.…”
Section: Management Of Mafld-related Hccmentioning
confidence: 99%
“…In der aktuellen ESPEN-Leitlinie "Klinische Ernährung bei Lebererkrankungen" wird zur Bestimmung der Mangelernährung der Nutritional-Risk-Score (NRS 2002) oder Minimal Nutrition Assessment (MUST) oder The Royal Free Hospital Nutrition Prioritizing Tool (RFH-NPT) empfohlen. Sarkopenie bei Patienten mit HCC ist mit schlechter Therapieverträglichkeit sowie erhöhter Mortalität assoziiert [390][391][392][393][394]. Geringe Handkraftstärke und niedriger Phasenwinkel alpha (gemessen mit der Body-Impedance-Analyse) können Auskunft über ein erhöhtes Mortalitätsrisiko geben [395].…”
Section: Leitlinieunclassified